2012
DOI: 10.5267/j.msl.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Ranking important factors on information technology in development free zone markets: An AHP implementation

Abstract: Information technology (IT) plays a vital role on developing different markets. In this paper, we study the impact of IT on developing businesses located mainly on free zones or in the borders of countries using analytical hierarchy process. The proposed study of this paper gathered the relative importance of five important factors influencing IT implementation. There are 12 experts and we use pairwise comparison to gather their insight and using Expert Choice we implement AHP for ranking the factors. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…There have been several studies on detecting barriers on development of free zones in the world. Azad and Rostamnya (2012a), for instance, studied the effect of information technology (IT) on development of businesses located mainly on free zones or in the borders of countries using analytical hierarchy process. The results of their survey have indicated that management was the most important factor, followed by cultural and social items.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies on detecting barriers on development of free zones in the world. Azad and Rostamnya (2012a), for instance, studied the effect of information technology (IT) on development of businesses located mainly on free zones or in the borders of countries using analytical hierarchy process. The results of their survey have indicated that management was the most important factor, followed by cultural and social items.…”
Section: Introductionmentioning
confidence: 99%